Elevated temperature lasing from injection microdisk lasers on silicon. (18th December 2017) - Kryzhanovskaya, N V; Moiseev, E I; Polubavkina, Y S; Maximov, M V; Mokhov, D V; Morozov, I A; Kulagina, M M; Zadiranov, Y M; Lipovskii, A A; Tang, M; Liao, M; Wu, J; et al.
Abstract: The combination of high operation temperatures and small diode lasers directly grown on silicon substrates is essential for their application in future photonic integrated circuits. In this letter, results are presented for quantum dot III–V-on-Si microdisk diode lasers tested at elevated temperatures. To the best of our knowledge, we have demonstrated the first uncooled microlasers with diameter of 30 µ m capable of operating in the continuous wave regime at 60 °C. In the lasing regime, the emission spectra contain one very intense line with a full-width at half-maximum of 30 pm; the side mode suppression ratio reaches 18 dB. Because of self-heating, the actual temperature of the active region is close to 100 °C. Under pulsed excitation, the maximal lasing temperature is 110 °C.